Bear in a square - Blackstone, Stella; Harter, Debbie (Cambridge, MA : Barefoot Books, 2006)
Young readers are challenged to find the squares, circles, hearts, ovals, diamonds, and other shapes in the colorful pictures.
1.3.
1.3
K-3
Keywords: Bears -- Juvenile fiction; Colors -- Juvenile fiction; Shapes -- Juvenile fiction; Bears -- Fiction; Color -- Fiction; Shape -- Fiction; Stories in rhyme; Bears -- Fiction; Color -- Fiction; Shape -- Fiction; Stories in rhyme; Picture books for children